Inter observer reliability for peritoneal carcinomatosis at computed tomography - Mahnoor Hafeez; Amjad Sattar; Waqas Ahmed Farooqui (Journal of the Pakistan Medical Association, 2023)
Objective: To determine whether there is inter-observer reliability between radiologists for reporting peritoneal carcinomatosis and computed tomography peritoneal carcinomatosis index estimation. Method: The retrospective, cross-sectional study was conducted at Dow Institute of Radiology, Dow University of Health Sciences (DUHS), Ojha campus and comprised computed tomography scans done between December 1, 2019, to May 31, 2020, that were extracted from the institutional database searched using key words ‘peritoneal carcinomatosis’ and/or ‘serosal deposits’. The first readers had 1-4 years of post-fellowship experience, while the 2nd readers were senior radiologist. Inter-observer reliability was assessed quantitatively and qualitatively for 15 peritoneal sites using, among other tolls, the Sugarbaker computed tomography peritoneal carcinomatosis index. Data was analysed using SPSS 21. Results: Out of 236 subjects with mean age 53.6±13.6 years, there were 173(73.3%) females and 63(26.7%) males. The most common primary cancer was ovarian 145(61.4%), followed by colon 26(11%). The size of peritoneal deposit was not reported in 75(31.8%) cases. Of the 15 sites analysed, good agreement was not found in 7(46.7%). There was an excellent intra-class correlation for measuring computed tomography peritoneal carcinomatosis index scores among the radiologists irrespective of the grade of the faculty (>0.90). Conclusion: The inter-observer reliability was low, but good agreement for computed tomography peritoneal carcinomatosis index would encourage radiologists to use it in peritoneal cancer reporting. Key Words: Computed tomography, Inter-observer reliability, Peritoneal carcinomatosis, Reporting, Agreement.